Prediction of the hobbing cutting forces from a thermomechanical modeling of orthogonal cutting operation. (August 2016) - Sabkhi, Naoual; Moufki, Abdelhadi; Nouari, Mohammed; Pelaingre, Cyril; Barlier, Claude
Highlights: Modeling of gear hobbing process. Coupled approach to predict cutting forces during the finishing hobbing process. Analyze of the triboligical conditions at the tool-chip interface. Abstract: The common external cylindrical gears are manufactured by gear hobbing process. The particularity of this operation is due to the nature of the interaction between the tool cutting edge and the workpiece material which is more complex than in conventional machining operations such as turning, milling or drilling. This can affect significantly the thermomechanical process of the chip formation. The main goal of this paper is to propose a coupled approach to analyze accurately the cutting edge effect and to predict the evolution of cutting forces during the finishing hobbing process. This model is based on two parts: (i) during the hobbing operation, the evolution of the undeformed chip section generated by each hob's tooth is determined from the CAD geometrical simulations and (ii) the cutting forces are calculated from a mechanistic model. In this mechanistic approach, the specific force coefficients (cutting and edge effects) have been determined from a thermomechanical model, based on the ALE (Arbitrary Eulerian Lagrangian) approach, by considering the material characteristics such as strain rate sensitivity, strain hardening and thermal softening. It can be noted that the ALE approach allows to accurately take into account accurately the cutting edge effect and to analyze the triboligical conditions at the tool-chip interface (i.e. the contact nature: sliding, sticking or sticking-sliding contact). Indeed, this kind of information is of great importance to analyze the effect of cutting condition on the tool wear. The numerical and experimental results are compared for several cutting velocities in orthogonal process. The present approach leads to a three dimensional cutting force model for hobbing process and appears as an interesting alternative to the classical mechanistic approach which requires many experimental tests to determine the cutting force coefficients. Finally, the proposed model has been applied to analyze a finishing hobbing gear with very large sizes (several meters).